(untitled) (Proceedings of Voronezh State University. Series: Geology, 2021)
Introduction: As fields with a relatively low grade of gold deposits have become involved in processing, there is a primary task of modernising the existing technologies of enrichment of ores of the Sukholozhsk type, which will allow reducing the cut-off grades, and hence capitalising the projected companies. This technology involves super grinding by means of cavitation. Methodology: Super grinding in neutral and chloride solutions was carried out using a cavitation system of a rotary type with the constant measurement of temperature, time, and pH. Determination of the valuable components was carried out by a QUANT-Z-ETA-1 atomic absorption spectrometer (OOO Kortek, Russia). Silicate analysis was performed by a S8 Tiger X-ray diffractometer (Bruker AXS GmbH, Germany). Electron probe microanalysis with scanning electron microscopy was conducted by a JSM-6510LV electron microscope (JEOL Ltd., Japan) and an INCA Energy 250 microanalysis system (Oxford Instruments, UK). Sample preparation was common for mixed acid (aqua regia), granulometric composition was according to GOST 12536-2014, physical characteristics were according to GOST 5180-2015. Results and discussion: Before and after the cavitation treatment in neutral and acidic environments, two samples, which represent the products of different alternatives of technological conversion (sorption and flotation tailings), were studied to determine the kinetics of the recovery of precious components. As a results of these experiments, graphs of the changes in the granulometric composition after the process of cavitation were created and the degree of influence of the cavitation processes on precious metals (gold and platinum) was determined. Conclusions: Ores in the Krasnoe field were formed under the conditions of upwelling facies on the passive continental margin. As a result, a complex with high contents of organic carbon was formed. It is both of terrigenous and aquagenic origin. Due to the extraction of nanoscale gold in the process of super grinding in a chloride environment, cavitation allows improving its recoverability, as well as ensuring the transition of platinum in a solution. However, it causes a problem, that of increasing carbon activity.